2010
DOI: 10.2223/jped.2035
|View full text |Cite
|
Sign up to set email alerts
|

Use of stem cells in perinatal asphyxia: from bench to bedside

Abstract: Objectives: To present recent scientific evidence on the effects of stem cell transplantation in animal models of neonatal hypoxic-ischemic brain injury and address the translational relevance of cell therapy for clinical application in this context. Sources:The PubMed and Scopus databases were used to select articles. The selection criterion was the specificity of articles regarding the subject studied, preferably articles published from 2000 onward. We also reviewed classic articles from previous years that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…151,152 Animal studies support the idea that cord blood and mesenchymal stem cells, cell types that are available in a clinical setting, have a neuroprotective effect in neonatal HIE. 153 These effects have been attributed to immunomodulation, activation of endogenous stem cells, release of growth factors, and antiapoptosis mechanisms.…”
Section: Neuroprotection Mediated By Hypothermiamentioning
confidence: 95%
“…151,152 Animal studies support the idea that cord blood and mesenchymal stem cells, cell types that are available in a clinical setting, have a neuroprotective effect in neonatal HIE. 153 These effects have been attributed to immunomodulation, activation of endogenous stem cells, release of growth factors, and antiapoptosis mechanisms.…”
Section: Neuroprotection Mediated By Hypothermiamentioning
confidence: 95%
“…Owing to the poor survival of the transplanted cells and little evidence for neural differentiation, bystander effects have been postulated to be the main mechanisms for functional recovery after CB transplantation, including release of neurotrophic factors to stimulate endogenous neurogenesis, prevention of cell loss and immunomodulation (Figure 4). 17,97,98 It has also been suggested that stem cell engraftment in the brain may not be critical for functional recovery provided that neurotrophic factors secreted by exogenous cells could reach the ischemic brain. 93 However, in most of the animal studies, human CB cells were injected without prior or concomitant immunosuppression.…”
Section: Animal Models Of Human Cb Transplantation For Hiementioning
confidence: 99%
“…Stem cells, which are self-renewing and considered the most primordial and least committed cells offer significant promise for treating perinatal brain injury (Kennea and Mehmet, 2004;Santner-Nanan et al, 2005;Vawda et al, 2007;Ikeda, 2008;de Paula et al, 2010; given their anti-inflammatory (Li et al, 2005;Murphy et al, 2010;Kim et al, 2012), trophic (van Velthoven et al, 2012Fu et al, 2017), and regenerative (Ilancheran et al, 2007;van Velthoven et al, 2010;Donega et al, 2014) capabilities. Indeed, neonatal models of hypoxic brain injury using different stem cell types support their therapeutic utility (van Velthoven et al, 2010(van Velthoven et al, , 2012Kim et al, 2012;Donega et al, 2014) and presently there are several adult stroke clinical trials underway (e.g., clinical trials registry numbers: NCT02605707, NCT01151124, NCT04434768, NCT02980354).…”
Section: Perinatal Brain Injurymentioning
confidence: 99%